An experimental study of the air-side performance of a novel louver spiral fin-and-tube heat exchanger - Kiatpachai, Parinya; Keawkamrop, Thawatchai; Asirvatham, Lazarus Godson; Mesgarpour, Mehrdad; Dalkilic, Ahmet Selim; Ahn, Ho Seon; Mahian, Omid; Wongwises, Somchai (ELSEVIER, 2022)
We studied the effect of fin patterns on the air-side performance of a novel type of heat exchanger, namely louver spiral fin-and-tube heat exchangers (LSFTHXs). We investigated three types of fin patterns-radial, curved, and mixed-louver spiral fins-and compared their characteristics with plain spiral fin. We fabricated heat exchangers with a crimped aluminum fin base, two rows of steel tubes, and a fin pitch of 8.45 mm. All heat exchangers had both multipass parallel and counter cross-flow arrangements. The average heat transfer rate (Q(ave)), heat transfer coefficient (h(o)), and pressure drop (delta P) increased along with frontal air velocity. The louver-spiral fin provided greater Q(ave) and h(o) than plain-spiral fin by about 9.7-15.6% and 13.4-27.1%, respectively. The j factors (Colburn factors) of louver-spiral fins were greater by approximately 10.4-13.1% (for mixed LSFTHX), 7.7-8.8% (for radial LSFTHX), and 2.1-5.1% (for curved LSFTHX) compared with the plain SFTHXs. Additionally, we found no significant difference in delta P or f factor (friction factor) between louver-spiral and plain-spiral fins. LSFTHX configurations increased ho and j. (C) 2022 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Alexandria University
Keywords: Heat exchanger; Spiral fin; Louver fin; Spiral fin and tube heat exchanger; FLOW CHARACTERISTICS; THERMAL PERFORMANCE; MULTIPASS PARALLEL; PITCHES; Engineering